Dynamics of indexes of carbohydrate exchange at patients by saccharine diabetes of 2th type on a background application of facilities of physical rehabilitation - Калмиков [Kalmikov S.], Сергій Андрійович (Slobozhanskyi Herald of Science and Sport, 2012)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> In this work it is presented the results of using of physical rehabilitation means for complex therapy of diabetes mellitus with the purpose of achievement of stable compensation for carbohydrate metabolism. It was determined that application of remedial gymnastics with physical exercises containing the elements of yogic asanas, yogic respiratory exercises and respiratory exercises taking into consideration the tone of simpathics and parasimpathics parts of the vegetative nervous system of these patients and dosed walking resulted in the more stablenormoglicemia in patients with diabetes mellitus. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->